Supplementation with Bioactive Compounds Improves Health and Rejuvenates Biological Age in Postmenopausal Women - Estefanía Díaz-Del Cerro; Judith Félix; Mª Carmen Martínez-Poyato; Mónica De la Fuente (Biomolecules)
Aging involves immune system deterioration (immunosenescence) and increased oxidative stress, both associated with morbidity and mortality. Menopause accelerates aging, highlighting the need for strategies to mitigate its effects in postmenopausal women. This study assessed the impact of daily oral supplementation for one month with 39 bioactive compounds (UNAMINA)—including amino acids, vitamins, and antioxidants—on immune function, redox parameters, stress-related hormones, and biological age in healthy postmenopausal women. Peripheral blood samples were collected before and after supplementation to analyze lymphocyte and neutrophil functions (adherence, chemotaxis, natural killer cell antitumor capacity, and lymphoproliferative response to mitogens), oxidative stress markers (antioxidant defenses such as glutathione peroxidase (GPx) and reductase activities, reduced glutathione (GSH) concentrations, as well as oxidants such as oxidized glutathione (GSSG), and lipid peroxidative damage) in blood cells, and stress-related hormones (dehydroepiandrosterone (DHEA) and cortisol) in plasma. Supplementation improved all immune cell functions and decreased oxidative stress (increasing antioxidants defenses such as GPx activity and GSH concentration and decreasing GSSG amount) and cortisol concentrations, whereas those of DHEA increased. The biological age also decreased. The results suggest that these bioactive compounds may be a beneficial strategy for promoting healthier aging in postmenopausal women by enhancing immune function, reducing biological age, improving redox balance, and regulating stress hormones.